”Generation and Maintenance of Listeria-specific CD8+ T cell Responses in Perforin-Deficient Mice Chronically Infected with LCMV” - Humphreys, Troy D. (2007)
Disruption of the perforin gene results in primary immunodeficiency and an increased susceptibility to opportunistic pathogens. Perforin-deficient (PKO) mice fail to clear primary lymphocytic choriomeningitis virus (LCMV) Armstrong, resulting in persistent infection and functional exhaustion of virus specific CD8+ T cells. CD8+ T cell responses to Listeria monocytogenes (LM) challenge within the first week after LCMV infection were diminished in both WT and PKO mice, and correlated with enhanced bacterial clearance. However, bacterial challenge at later time points generated similar CD8 T cell responses in both groups of mice. The phenotype and function of pre-existing LM-specific memory CD8+ T cells were maintained in persistently infected PKO mice. Thus persistent LCMV infection, as a result of perforin deficiency, results in dysfunction of the virus-specific CD8+ T cell response but does not compromise the host's ability to maintain pre-existing memory CD8+ T cells or to generate new memory CD8+ T cell responses against other pathogens.